Interaction of ultrasonic waves with partially-closed cracks in concrete structures. (10th April 2018) - Pahlavan, Lotfollah; Zhang, Fengqiao; Blacquière, Gerrit; Yang, Yuguang; Hordijk, Dick
Highlights: The interaction of ultrasonic waves with partially-closed cracks in concrete has been studied. The influence of crack opening and incident angle on the signal features has been evaluated. The width of the crack process zone has been estimated from the data. The anisotropy of the material at the crack zone has been quantified. Abstract: Interaction of ultrasonic waves with partially-closed surface-breaking cracks in concrete structures has been studied. Measurements have been conducted on a reinforced concrete beam containing various mechanical-load-induced cracks and compared with the baseline measurements at those locations. Influence of crack width, incident angle of waves with cracks, and distance from the cracks on travel time and amplitude of the waves have been investigated when the beam was unloaded. It has been observed that a measurable part of the waves propagate through the cracks due to the acoustic coupling between the crack faces, although attenuation can be relatively high. The travel time has shown a nearly independent behavior from remaining crack opening in the measured range of 0.05 mm to 3 mm. Measurements in directions orthogonal and parallel to the crack suggest that there is substantial anisotropy in the cracking zone. Furthermore, an effective width of the micro-cracking area around the cracks has been estimated from the measurements.